EFFECT OF STUDY SKILL TRAINING AND MULTIPLE INTELLIGENCE INTERVENTION IN ENHANCING READING HABIT OF JUNIOR SECONDARY SCHOOL STUDENTS IN IBADAN, NIGERIA (2017)
Reading plays a vital role in the educational attainment of students. However, poor reading habit among students is a great concern to the society. This habit undermines the educational attainment and career actualization of most students. Literature has focused on the factors precipitating poor reading habit with little emphasis on intervention efforts in Nigeria. Therefore, the objective of this study was to investigate the effectiveness of Study Skill Training (SST) and Multiple Intelligence Intervention (MII) in enhancing reading habit of junior secondary school students in Ibadan, Nigeria. The moderating effect of gender and academic self-efficacy were also examined. Bandura’s Social Cognitive Theory served as the framework. A pre-test-post-test, control group, quasi-experimental design with a 3x2x3 factorial matrix was adopted. Purposive sampling technique was used to select a secondary school each from Ibadan North, Ibadan South West and Ibadan South East respectively. The participants below 15 years accounted for 76.1% while the participants above 15 years accounted for 23.9%. The selected schools were each assigned to SST, MII and the Control groups. Ninety participants across the three secondary schools who scored below 30 out of 60 marks in the screening exercise were randomly selected for the study but eighty-eight completed the programme. The participants were randomly assigned to SST (28), MII (30) and Control (30).The training lasted for two months. Cognitive Style (r = 0.78), Reading Habit (r =0.89) and Academic Self-Efficacy (0.91) scales were used for data collection. Analysis of covariance and Scheffe post hoc test were used to analyse the data. Study skill training and Multiple intelligence intervention had significant main effect on reading habit (F(2, 71) = 53.25,partial ŋ2 = 0.60). Reading Habit mean scores of the participants in the experimental groups, MII ( ̅= 44.43) and SST ( ̅= 41.17) increased significantly than those in the Control group ( ̅= 23.73).The percentage of female participants was 53.4 while the percentage of male participants was 46.6. Gender had a significant main effect on reading habit among the participants (F(1, 71) = 5.163, partial ŋ2 = .07). Females ( ̅= 38.66 ) have improved reading habit than their male counterparts ( ̅=33.51). There was no significant main effect of academic self-efficacy on reading habit. There was no significant two-way interaction effect of treatment and gender in enhancing reading habit. Also, there was no significant two-way interaction effect of treatment and academic self-efficacy on reading habit. There was no significant three-way interaction effect of treatment, academic self-efficacy and gender on reading habit. Study skill training and Multiple intelligence intervention were effective in enhancing reading habit of junior secondary school students. Multiple intelligence intervention was more effective. Educational and counselling psychologists should constantly assist students to improve their reading habit using these interventions. Keywords: Study skill training, Multiple intelligence intervention, Reading habit, Junior secondary school students, Word count: 498